Ultradeep hydrodesulfurization of fuel over superior NiMoS phases constructed by a novel Ni(MoS4)2(C13H30N)2 precursor. Issue 17 (12th August 2020) - Xu, Jundong; Wen, Chenglong; He, Shuisen; Fan, Yu
Abstract : Ni(MoS4 )2 (C13 H30 N)2 was synthesized and adopted for preparing a NiMoS/γ-Al2 O3 hydrodesulfurization catalyst, and the as-prepared catalyst exhibits superior 4, 6-dimethyldibenzothiophene hydrodesulfurization activity. Abstract : This article presents novel decyltrimethylammonium bromide-dispersed Ni–Mo sulfide (DTMA-NiMo) as a precursor for preparing an efficient NiMoS/γ-Al2 O3 hydrodesulfurization (HDS) catalyst. The as-synthesized DTMA-NiMo is a sulfide containing both long-chain quaternary ammonium and Ni–Mo–S elements. The proposed method not only significantly improves the dispersion of Mo species but also greatly promotes the incorporation of Ni into MoS2 slabs, leading to an increase in the number of NiMoS phases. As a result, the DTMA-NiMo-based NiMoS/γ-Al2 O3 catalyst exhibits much higher activity for the HDS of 4, 6-dimethyldibenzothiophene (4, 6-DMDBT) and fluid catalytic cracking (FCC) diesel than NiMoS/γ-Al2 O3 catalysts prepared by the co-impregnation and tetrapropylammonium bromide (TPAB)-assisted methods. This novel strategy sheds a light on the facile and low-cost preparation of superior NiMoS phases without sulfidation treatment.